Integrating Information Behaviour and Information Literacy During Academic Tasks: A Comparative Study of Japanese and Canadian Undergraduate Students in Canadian Universities - Ishimura, Yusuke; Bartlett, Joan C. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This presentation reports preliminary results from doctoral research that investigates the information behaviour and information literacy skills of Japanese and Canadian undergraduate students during their research tasks in Canadian universities. Differences and similarities in behaviours and skills between the two groups are identified through analysis of research portfolios and interviews. Cette communication présente les résultats préliminaires d'une étude doctorale portant sur le comportement informationnel et la maîtrise de l'information des étudiants japonais et canadiens de premier cycle lors de leurs travaux de recherche dans les universités canadiennes. Les différences et les similitudes dans les comportements et les habiletés des deux groupes sont décelées au moyen de l'analyse des dossiers de recherche et d'entrevues.